Illegal Online Loans: Between Generation Millenial GAP and Regulatory Challenges in Indonesia - Yuditia Prameswari; Izura Rochma (Jurnal Restorasi : Hukum dan Politik, 2024)
The purpose of this study is to identify the voids in knowledge regarding the use of unauthorised online loans by millennials and to comprehend the regulatory obstacles the government must surmount to combat this problem. Therefore, this study aims to provide a contribution towards endeavours that seek to diminish the prevalence of illicit online loans and enhance public consciousness regarding the perils linked to this activity. A literature review serves as the primary research method in order to gather information and conduct an in-depth analysis concerning the millennial generation's exposure to the phenomenon of unlawful online lending. Subsequently, the outcomes of this examination are succinctly documented in a research report that encompasses an overview of the issue's context, a review of pertinent literature, an evaluation of discovered results, conclusive remarks, and policy suggestions aimed at safeguarding the millennial generation against unauthorised online lending.